Towards self-powered technique in underwater robots via a high-efficiency electromagnetic transducer with circularly abrupt magnetic flux density change. (15th November 2021) - Li, Zhongjie; Jiang, Xiaomeng; Yin, Peilun; Tang, Lihua; Wu, Hao; Peng, Yan; Luo, Jun; Xie, Shaorong; Pu, Huayan; Wang, Daifeng
Graphical abstract: Highlights: A compact electromagnetic transducer harnessing ocean-current flow energy. Half-watt-level output power with a high energy conversion efficiency of 35.38%. Originally constituting circularly abrupt magnetic flux density change. Self-technique for underwater robot energy replenishment. High performance on charging lithium batteries and millifarad capacitors. Abstract: In this article, we present a high-efficiency electromagnetic transducer harvesting kinetic energy from the ocean current for self-powered technique in underwater robots to tackle the electric energy replenishment problem. A circular magnet array with alternating magnet arrangement was employed for providing a sudden change in magnetic flux density. A gear train was introduced into the compact design to greatly increase the rotation speed of the rotor. The finite element method is used to simulate and compare the magnetic flux density distributions and the induced voltages in the coil under different magnet arrays (conventional Halbach magnet array and proposed alternating one) with different magnet dimensions and numbers. The finite element method analysis shows that the alternating array displays a much larger changing magnetic flux density rate resulting in high induced electromotive forces. The experimental results based on a fabricated prototype indicate that the transducer yields maximum average output power of about 0.51 W with an energy conversion efficiency of 30.91% under the water flow speed of 0.64 m/s with a load resistance of 1 kΩ. We also investigated the capability of the transducer for self-powered applications in underwater robots. The transducer charged a 20 mF capacitor from 0 V to 29 V in 50 s. Also, the prototype charged a lithium battery embedded inside an underwater robot by 75% within 400 s. This study, with a broad application prospect, can advance the future development of self-powered underwater robotic systems.